Vitrification of Rhesus Macaque Mesenchymal Stem Cells and the Effects on Global Gene Expression. (24th October 2017) - Fu, Xufeng; Yan, Yaping; Li, Shanshan; Wang, Junfeng; Jiang, Bin; Wang, Hong; Duan, Yanchao; Tan, Tao; Gao, Fei; Gong, Desheng; Niu, Yuyu; Ji, Weizhi; et al.
Abstract : Mesenchymal stem cells (MSCs) are one of the most promising adult stem cells for clinical application in a cell therapy. The development of large-scale cryopreservation techniques, such as vitrification, for MSCs is a prerequisite for clinical therapies. Dimethyl sulfoxide (DMSO) and ethylene glycol (EG) are two types of cryoprotectants widely used for cell vitrification. However, the effects of DMSO and EG on the biological characteristics and transcriptome profiles of MSCs after cryopreservation remain unknown. In the present study, the viability, immunophenotype of cell surface markers, proliferation, differentiation potency, and global gene expression of rhesus macaque bone marrow-derived MSCs vitrified using DMSO and EG were studied. The results showed that vitrification did not affect the morphology, surface markers, and differentiation of the MSCs, and compared to DMSO, EG better protected cell viability and proliferation. Most importantly, vitrification resulted in changes in a large number of transcripts of MSCs either preserved using DMSO or EG. This report is the first to examine the effects of DMSO and EG on global gene expression in stem cells. These results will be beneficial to understanding the biological process involved in MSC vitrification and will contribute to improving cryopreservation protocols that maintain transcriptomic identity with high cryosurvival for preclinical research and clinical long-term storage.